Experimental investigation of forced convective condensation heat transfer of hydrocarbon refrigerant in a helical tube. (25th January 2018) - Yu, Jiawen; Chen, Jie; Li, Fengzhi; Cai, Weihua; Lu, Laiyu; Jiang, Yiqiang
Highlights: A new experimental facility was designed to directly measure the wall temperature along a helical tube. The effect of mass flux, vapor quality, heat flux on the two-phase heat transfer or frictional pressure drop were analyzed. Several prediction correlations were used to compare the experiment results. Abstract: In this paper, the characteristics of two-phase heat transfer and frictional pressure drop for hydrocarbon refrigerant propane condensation in a helical tube were experimentally investigated. A new experimental facility was designed to directly measure the wall temperature along a helical tube with the hydraulic diameter of 10 mm. The experimental conditions were set as: mass flux from 200 to 400 kg/(m 2 ·s), heat flux from 1.4 to 9.6 kW/m 2 and saturated temperatures from −40 to 27 °C. Also, the effects of mass flux and vapor quality on heat transfer coefficient and frictional pressure drop were studied. Compared with the experimental data, it showed that Shah correlation could well predict heat transfer coefficients within a mean deviation of ±20%, and Friedel correlation and Müller-Steinhagen & Heck correlation both well predicted frictional pressure drop with a mean deviation less than ±20%. These results will provide important instructions for the tube-side design of spiral wound heat exchanger.